Students' Interest in Non-Formal Education; Case Study at Madrasah Diniyah Awaliyah Darul Ulum Al-Ihsani - Muthoharoh Muthoharoh; Silfiya Atiqoh (Jurnal Ilmiah Iqra', 2022)
Students' Interest in Non-Formal Education; Case Study at Madrasah Diniyah Awaliyah Darul Ulum Al-Ihsani. Students' interest in madrasah diniyah is decreasing even though this religious college has been developing for quite a long time. The purpose of this qualitative research is to ascertain the state of the Sumbaga Village community, students' interest in MDA Darul Ulum Al-Ihsani Sumbaga Village, and the state of MDA Darul Ulum Al-Ihsani Sumbaga Village. The subjects of this study were the foundation's head, the madrasa's head, and the Darul Ulum Al-Ihsani MDA teacher, parents and students who dropped out and did not continue to MDA, students who were still in MDA school, and their parents. Data on student interests was collected through interviews, observations, and documentation. The collected data was analyzed in three stages: data reduction, data display, and conclusion and verification. The results of this study show that the Sumbaga Village community is in good shape in terms of religion, education, and the economy, as well as the infrastructure owned by MDA Darul Ulum Al-Ihsani, but student interest in learning remains low due to students' poor physical condition and family economy, for example. Following up on the study's findings, a unique strategy is required to increase students' interest in non-formal education at MDA Darul Ulum Al-Ihsani from both madrasas and students' parents